The Pragmatics of Political Claims and Social Responses amidst Covid-19 and EndSARS Saga in Nigeria - Onwubiko, Chioma (International Journal of Language and Literary Studies, 2021)
There have been few stand-alone linguistic studies on the Covid-19 virus and the 2020 EndSARS protests in Nigeria. The present study intersects these two critical events with particular focus on the political claims made by the ruling class and the corresponding social responses in line with the contextual affordances shared by the participants. Searle’s speech act theoretic approach is adopted to analyse the pragmatic intentions of the illocutionary acts which political claims perform while Juvenalian satire is used to discuss the satirical elements embedded in the social responses in a bid to ridicule leadership follies and abuses. Three popular Nigerian online Newspapers and few comments from Facebook are selected for this study. Their selection is based on their coverage of these events, coverage of these political claims and popular readership evidenced in the social responses. In all, a total of 6 political claims and 25 social responses relevant to this study are analysed. The study revealed that the pragmatic relevance of these claims is embedded in its political functions of wielding undue influence over the populace, making promises driven by rhetoric and short of initiative and calculated reticence in response to social issues. Consequently, the social responses highlight and criticise leadership vices and the weak efforts of the government in dispensing its leadership interventions. It also fulfils communicative purposes of the contextual space, promote solidarity among the people while prompting change in the political class and the society at large.